Tightening the Life-Cycle Construct: A Taxonomic Study of Growth Stage Configurations in High-Technology Organizations - Hanks, Steven H.; Watson, Collin J.; Jansen, Erik; Chandler, Gaylen N. (Entrepreneurship Theory and Practice, 1994)
Over the years much has been written about the organization life cycle, yet there has been remarkably little attention given to the underlying construct of a life-cycle stage. It is proposed in this study that each life-cycle stage consists of a unique configuration of variables related to organization context and structure. Cluster analysis is used to derive a taxonomy of growth stage configurations in a sample of 126 high-technology organizations. The derived configurations suggest a sequence of four growth stages.